Dual-Species Model Biofilm Consisting of Listeria monocytogenes and Salmonella Typhimurium: Development and Inactivation With Cold Atmospheric Plasma (CAP) - Govaert, Marlies; Smet, Cindy; Walsh, James L.; Van Impe, Jan F. M. (Frontiers in Microbiology, 2019)
Most environmental biofilms contain a variety of species. These species can establish cooperative and competitive interactions, possibly resulting in an increase or a decrease in antimicrobial resistance. Therefore, results obtained following inactivation of single-species biofilms by means of different technologies (e.g., Cold Atmospheric Plasma (CAP)) should be validated for multi-species biofilms. First, a strongly adherent and mature L. monocytogenes and S. Typhimurium dual-species biofilm was developed by altering different incubation conditions, i.e., growth medium, incubation temperature, inoculum ratio of L. monocytogenes and S. Typhimurium cells, and incubation time. Adherence and maturity were quantified by means of optical density measurements and viable plate counts, respectively. Secondly, both the (one day old) reference biofilm and a more mature seven days old biofilm were treated for different CAP treatment times (0 - 30 min). Viable plate counts were again used to determine the (remaining) cell density. For both the biofilm development and inactivation, predictive models were applied to describe the growth/inactivation kinetics. Finally, the kinetics of the (one and seven day(s) old) dual-species biofilms were compared with those obtained for the corresponding single-species biofilms. Results implied that a strongly adherent and mature reference dual-species biofilm was obtained following 24 h of incubation at 25°C using 20-fold diluted TSB and an inoculum ratio of 1:1. Main observations regarding CAP inactivation were: (i) the dual-species biofilm age had no influence on the CAP efficacy, although a longer treatment time was required for the oldest biofilm, (ii) for the one day old biofilms, CAP treatment became less efficient for S. Typhimurium inactivation when this species was part of the dual-species biofilm, while L. monocytogenes inactivation was not influenced by the biofilm type, and (iii) for the seven days old biofilms, CAP inactivation of both species became more efficient when they were part of the dual-species biofilms. It can be concluded that the efficacy of the CAP treatment is altered when cells become part of a dual-species biofilm, which is quite important with respect to a possible application of CAP for biofilm inactivation within the food industry.